Global Lessons from a Local Reform: An Opinion on Teacher-Centric Implementation of National Curricula - Mazhar Sa’adi H. Sana; Katrina S. Salih; Al-Rashiff Hamjilani Mastul (Buletin Edukasi Indonesia, 2026)
In an era of global educational reform, the success of national curriculum overhauls hinges on frontline teacher perception and capacity. This opinion article examines the Philippine MATATAG Curriculum implementation through a qualitative case study of elementary teachers, framing it as a microcosm of universal challenges in educational change. Utilizing a descriptive-qualitative design with semi-structured interviews, the study explores teacher perceptions, identified challenges, and emergent opportunities. The conceptual framework centralizes teacher perception as the lens through which implementation dynamics, challenges, and opportunities are filtered and understood. Findings reveal a significant pedagogical shift towards learner-centeredness and foundational skills, warmly received yet hampered by systemic barriers including ambiguous objectives, insufficient resources, and inadequate training. However, teachers concurrently identify potent opportunities for creative pedagogy, localization, and workload efficiency. The discussion argues that curriculum reforms globally must pivot from a top-down policy dissemination model to a teacher-empowering, support-oriented ecosystem. Successful implementation is less about curricular content perfection and more about structured, respectful engagement with the professional wisdom and practical realities of teachers. This article concludes that investing in robust, continuous support systems and honoring teacher agency are non-negotiable prerequisites for translating ambitious curricular blueprints into enhanced learning competencies worldwide.